Acid Violence in Bangladesh: A Burning Issue and Devastating Violence against Women - Razzaque, Naimul; Saddat Raffat, Walid (International Journal of Scientific Research and Management (IJSRM), 2023)
Bangladesh is surrounded by a number of problems.Some of the fundamental issues also available in this country.Acid Violence is one of them,serious issue in Bangladesh.This paper means to recognize acid attack against women in perhaps one of the worst forms violation of morality and legal codes in the contemporary age.It is not because of its high frequency on women,rather because of its high frequency on women,rather beacause of its severe impact on the human body and mind.The rate of acid attacks though is decreasing in a satisfactory level,against women this rate is not yet satisfactory.Specialized collaboration to legislatures,non-administrative associations and different offices in this attemot should be emphatically advanced.